Acupuntura como tratamiento coadyuvante para tratar la xerostomía post radioterapia de cáncer de cabeza y cuello. - Martínez Barreto, Ambar Solange (2025)
The prevalence of head and neck cancer worldwide is alarming, and the established treatment is radiotherapy. Radiation therapy in cancer patients has several side effects, including xerostomia. This study aimed to analyze the effectiveness of acupuncture as an adjuvant therapy for treating xerostomia after radiotherapy for head and neck cancer by compiling documents from reliable research sources. Methodology: A search was conducted in databases such as PubMed, Scopus, and Web of Science using the PRISMA methodology and adhering to the inclusion criteria for the article search. Results: Nine articles were ultimately selected. Radiotherapy in patients with head and neck cancer directly affects the salivary glands. As the radiation dose increases, it damages the glandular acini and decreases salivary flow, causing xerostomia. Acupuncture may be effective for some patients and not for others, depending on one's belief in acupuncture therapy. Conclusion: Acupuncture as an adjuvant treatment for post-radiation xerostomia for head and neck cancer is effective as long as the auricular points are stimulated. However, more up-to-date information on the subject is needed.